Blockchain based land registry with Delegated Proof of Stake (DPoS) consensus in Bangladesh - Shahriyer, Mohammad Muhtasim; Monim, Mobashir (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.